2018
DOI: 10.1155/2018/1380146
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydroxystilbene Glucoside Effectively Prevents Apoptosis Induced Hair Loss

Abstract: The effect of Polygonum multiflorum against hair loss has been widely recognized. 2,3,5,4′-Tetrahydroxystilbene-2-O-β-D-glucoside (TSG) is the main component of Polygonum multiflorum; however, its role in hair regeneration has not been established. To evaluate the hair growth-promoting activity of TSG, depilated C57BL/6J mice were topically treated with normal saline, TSG, Pifithrin-α, Minoxidil for 2 weeks. In this study, we identified that p53, Caspase-3, Active Caspase-3, and Caspase-9 were obviously upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…no. 15596018; Thermo Fisher Scientific, Inc.) reagent on ice, followed by incubation for 5 min at 4˚C with RNAse for the inactivation of RNA enzymes (all the materials used for RNA treatment were performed as previously described ( 20 ). The samples were transferred into 1.5-ml Eppendorf tubes, followed by the addition of 400 µl chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…no. 15596018; Thermo Fisher Scientific, Inc.) reagent on ice, followed by incubation for 5 min at 4˚C with RNAse for the inactivation of RNA enzymes (all the materials used for RNA treatment were performed as previously described ( 20 ). The samples were transferred into 1.5-ml Eppendorf tubes, followed by the addition of 400 µl chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that TSG (30, 60 mg/kg) exerted antidepressant-like effects in mice by enhancing the hippocampal BDNF system ( Wang et al, 2017 ). Interestingly, it has also been shown that TSG (200 μM) has a significant hair-regeneration effect ( Chen et al, 2018a ). Because TSG could inhibit the p53-, Fas-, and Bax-induced apoptotic signaling pathways, thus preventing hair follicles from entering the catagen phase ( Chen et al, 2018a ).…”
Section: Pharmacological Properties Of Tsgmentioning
confidence: 99%
“…Especially, 2,3,5,4′-Tetrahydroxystilbene-2-O-β-D-glucoside (TSG) and emodin, single compounds identified in PM extract, were reported to show hair growth properties. TSG exerted anti-apoptotic effect in C57BL/6 murine follicles [16] and pharmacological effects on age related diseases, resulting in cardio-protective, neuro-protective and anti-hair loss [17]. Concretely, TSG acts as a protector of dopaminergic neurons by regulating Akt, GSK3β and Bcl2/BAD expressions as well as a hypotensive agent in vascular endothelial cells like minoxidil [18,19].…”
Section: Introductionmentioning
confidence: 99%